KARAKTERISTIK SARANG PENYU HIJAU (CHELONIA MYDAS) DI PULAU KASIAK KAWASAN KONSERVASI PENANGKARAN PENYU PARIAMAN, SUMATERA BARAT - Desi Nova Sari; Muhammad Fauzi; Eni Sumiarsih (Berkala Perikanan Terubuk, 2018)
The research aimed to understand the nesting area characteristic of C. mydas in the Kasiak Island was conducted from March-April 2017, coincidence with the nesting time of green turtle. Observation of the nesting area of green turtle was conducted in the Northern, Southern, Western and Eastern parts of the island. Parameters studied were the slope of the beach, the distance between the water edge during the high tide and the nest, sand texture, types of vegetations around the nest, number of nests present and the quality of water around the island.  Results shown that the coast’s slope ranged from 1.74 to 2.890, the distance between the water edge during the high tide and the nest ranged from 1.17 to 1.70 m, the substrate texture was dominated by sand (> 90%), silt (3.4-7.25%) and clay (2-8%).  The nest temperature was 25-320C, nest humidity was 30-40% and the common vegetation was Thespesia populnea.  Quality of the water  around the Kasiak Island are as follows: temperature was 29-300C, salinity was from 33-34 ‰, current speedwas 0.4-0.5 m / s and pH was 8.